Neuroanatomical and neurocognitive changes associated with subjective cognitive decline - Rivas-Fernández, Miguel Ángel; Lindín, Mónica; Zurrón, Montserrat; Díaz, Fernando; Lojo-Seoane, Cristina; Pereiro, Arturo X.; Galdo-Álvarez, Santiago (Frontiers in Medicine, 2023)
Introduction: Subjective Cognitive Decline (SCD) can progress to mild cognitive impairment (MCI) and Alzheimer´s disease (AD) dementia and thus may represent a possible preclinical stage of the AD continuum. However, evidence about the brain structural changes observed during SCD remains inconsistent. Method: This cross-sectional study was aimed to evaluate, in subjects recruited from the CompAS project, neurocognitive and neurostructural differences between a group of forty nine control subjects and forty nine individuals who met the diagnostic criteria of SCD and showed high levels of subjective cognitive complaints (SCCs). Structural magnetic resonance imaging was used to evaluate neuroanatomical differences in brain volume and cortical thickness between both groups and also to evaluate how these neuroanatomical changes are related to cognition. Results: Relative to the Control group, the SCD group displayed structural changes involving frontal, parietal and medial temporal lobe regions of critical importance in AD aetiology and functionally related to several cognitive domains, including executive control, attention, memory and language. Conclusion: Despite the absence of clinical deficits, SCD may constitute a preclinical entity with a similar (although still subtle) pattern of neuroanatomical changes to that observed in individuals with amnestic MCI or AD dementia.